2023
DOI: 10.1101/2023.02.14.528526
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell class-specific electric field entrainment of neural activity

Abstract: Electric fields affect the activity of neurons and brain circuits, yet how this interaction happens at the cellular level remains enigmatic. Lack of understanding on how to stimulate the human brain to promote or suppress specific activity patterns significantly limits basic research and clinical applications. Here we study how electric fields impact the subthreshold and spiking properties of major cortical neuronal classes. We find that cortical neurons in rodent neocortex and hippocampus as well as human cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The negative slopes at the higher frequencies of the PLV curves also need an explanation. An excellent study by Lee et al demonstrated, with intracellular recordings of the transmembrane voltage in cortical cells, that the passive membrane parameters do not filter the extracellular AC fields at subthreshold membrane voltages (Lee et al, 2023). Thus, the decline in the PLV plots above 100 Hz (Figure 8) should not be because of passive filtering of high frequencies by the cell membrane at the PC level.…”
Section: Frequency Tuningmentioning
confidence: 94%
“…The negative slopes at the higher frequencies of the PLV curves also need an explanation. An excellent study by Lee et al demonstrated, with intracellular recordings of the transmembrane voltage in cortical cells, that the passive membrane parameters do not filter the extracellular AC fields at subthreshold membrane voltages (Lee et al, 2023). Thus, the decline in the PLV plots above 100 Hz (Figure 8) should not be because of passive filtering of high frequencies by the cell membrane at the PC level.…”
Section: Frequency Tuningmentioning
confidence: 94%
“…This kind of ephaptic coupling has been proposed as a global control mechanism that can help coordinate neuronal activity (Pinotsis et al, 2023;van Bree et al, 2024). Oscillations of electrical potential are thought to play a similar role, enabling selective communication across brain areas, allowing multiplexed signal transmission, and entraining the timing of neural firings with perceptual or behavioral variables of interest (Buzsaki, 2006;Lee et al 2024;van Bree et al, 2024).…”
Section: Constraints As Causesmentioning
confidence: 99%
“…Nevertheless, neuronal morphology and biophysics are substantially different between cortical cell types within the same species [19,20]. Several works [21,22] have considered some cortical neurons with distinct cell classes and quantify their somatic polarization during weak oscillating EF stimulation with a fixed frequency to understand the field entrainment of spiking activity. Although growing studies have investigated the membrane polarization by tACS, how the frequency-dependent polarization varies between neocortical neurons and their subcellular categories is still not fully understand.…”
Section: Introductionmentioning
confidence: 99%